Historical Memory of the Kazakhs in the “Materials on Kyrgyz Land Use” - Abil, Ye.A.; Kuzembayuly, A. (KU Publ., 2022)
The statistical survey of the territories of Kazakhstan in the late 19th and early 20th centuries, the results of which were reflected in the “Materials on Kyrgyz (Kazakh) Land Use”, reflected not only the economic condition of Kazakh society but also the traditional historical memory. Historical legends reflect the time of their settlement in certain territories. These legends record the earlier settlements of the Kazakhs in the territories of Northern Kazakhstan — in the 14th–16th centuries. However, a number of written sources contradict the historical memory of the Kazakhs and point out the appearance of the Kazakhs in this territory only in the 17th–18th centuries. The reason for this is that Kazakh communities which declared their autochthonous origin were not part of the political system of the Kazakh Khanate until the 17th century and were known under the collective names “Nogai” and “Siberian Tatars”. “Materials” are an important source on the ethnic and political history of the Kazakh steppes in the 14th–18th centuries.
«Киргиз жерін пайдалану жөніндегі материалдарда» қазақтың тарихи жады
Историческая память казахов в «Материалах по киргизскому землепользованию»
Keywords: statistical expeditions; historical memory; historical consciousness; legends; Northern Kazakhstan; ethnic history; genealogies; Kazakhs; Siberian Tatars; Nogai